2019
DOI: 10.1002/ece3.5634
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and inferring behaviors using real‐time acceleration biotelemetry in reproductive steelhead trout (Oncorhynchus mykiss)

Abstract: Movement behaviors are central to ecology and conservation. Movement sensing technologies can monitor behaviors that are otherwise difficult to observe under field conditions and may enhance the ability to quantify behaviors at the population scale. We monitored steelhead trout (Oncorhynchus mykiss) spawning behaviors in a seminatural enclosure using accelerometer telemetry tags while simultaneously observing behaviors with underwater cameras. Behavioral assignments from visual observations were compared to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…For example, genetic stock identification and identification via parentage-based tagging [e.g., 46 , 68 ] of future telemetered fish would dramatically reduce the uncertainties associated with fish origin. Collection of additional fish trait and risk data, including physiological or transcriptomic measures of energetic status [e.g., 117 , 118 ], pathogen burden [e.g., 119 , 120 ], or stress indicators [e.g., 103 , 121 , 122 ], and quantification of individual thermal experience [e.g., 41 , 46 , 122 ] or activity budgets [ 123 ], would likely yield important insights on fish behaviors at the dams and on passage failure mechanisms. Tagging and monitoring individual fish has proven effective for assessing migration survival questions over large geographic areas [e.g., 124 126 ], but passive monitoring methods can also provide insight on failure mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, genetic stock identification and identification via parentage-based tagging [e.g., 46 , 68 ] of future telemetered fish would dramatically reduce the uncertainties associated with fish origin. Collection of additional fish trait and risk data, including physiological or transcriptomic measures of energetic status [e.g., 117 , 118 ], pathogen burden [e.g., 119 , 120 ], or stress indicators [e.g., 103 , 121 , 122 ], and quantification of individual thermal experience [e.g., 41 , 46 , 122 ] or activity budgets [ 123 ], would likely yield important insights on fish behaviors at the dams and on passage failure mechanisms. Tagging and monitoring individual fish has proven effective for assessing migration survival questions over large geographic areas [e.g., 124 126 ], but passive monitoring methods can also provide insight on failure mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…(Carbonara et al, 2015;Cooke et al, 2016;Lennox et al, 2017). Traditionally used in wild fish as a key source of information for conservation and management practices in aquatic ecology (Fuchs and Caudill, 2019;Lennox et al, 2017;McKenzie et al, 2016), these electronic tags are also a promising tool for refining farming procedures for a better monitoring and control of fish welfare in aquaculture facilities (Brijs et al, 2018;Carbonara et al, 2020Carbonara et al, , 2019aKolarevic et al, 2016;Martos-Sitcha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the process of building a redd can take several days for steelhead, including both the stage before and the stage after the spawning phase (Needham and Taft, 1934; Burner, 1951; Fuchs and Caudill, 2019). Thus one single sequence of pulses lasting 10–20 min will certainly not be enough to create a proper redd, and it is to be expected that there must be additional and extensive seismic redd‐building signals.…”
Section: Discussionmentioning
confidence: 99%